Padrão fermentativo e valor nutritivo de silagens de cana de açúcar produzidas durante o período da seca - Penso, Sarah (2020)
Among the alternatives for the use of sugarcane in animal feed, one can mention silage. There are some limiting factors that need to be considered, mainly due to alcoholic fermentation that can result in high losses of dry matter due to inadequate fermentation pattern. In this sense, the objective was to evaluate the fermentative characteristics and nutritive value of sugarcane silage produced during the dry period of the year. The design used was entirely randomized with four repetitions. The treatments were arranged in subdivided plots, considering as plot the varieties (RB925345; RB855453; RB855486; RB928064; RB867515), and as subplot the silage periods during the dry season (05/23; 07/04 and 08/15). The losses by gas and effluent, fermentative pattern of silage, bromatological composition were evaluated, as well as the in vitro incubation, in which gas production was measured, as well as the residues of DM and NDF, to calculate the IVDMD and IVDNDF. For all varieties and seasons the pH and ammonia nitrogen contents were adequate. In the dry period (August 15) occurred the lowest losses by effluents, contrary to the rain-dry transition period losses by gases. It is recommended based on the dry matter of the forage the ensiling of variety RB855453 in season 23.05; RB928064 and RB867515 in 04/07; RB855453 in 15/08. All varieties had similar behavior, with low contents of CP and MM in the silages obtained in different seasons. The highest contents of IVDMD and IVDNDF were observed for varieties RB835486, RB928064 and RB867515, which also had higher values of Vf. In the last season, there was a difference among varieties with regard to gas production rate, in which the variety RB835486 was estimated to have the highest value. Thus, it can be inferred that the highlighted variety was RB835486, with higher nutritional value of silage, being indicated for this purpose aiming its use in animal feed with productive potential.